Evaluating surgical strategies for pediatric congenital choledochal cysts: a multicenter retrospective study and network meta-analysis - Cao, Chuang; Xu, Zhibin; Cen, Long; Mai, Tianfu; Huang, Jihuang; Tian, Chuan (Frontiers in Pediatrics, 2025)
ObjectiveThis study compared the efficacy and safety of open, laparoscopic, and robotic-assisted surgeries for pediatric congenital choledochal cysts (CCC) using network meta-analysis, with retrospective cohort data to validate findings.MethodsFollowing the PRISMA guidelines, 28 cohort studies involving a total of 3,672 patients were included. Key outcomes assessed included operative time, hospital stay, intraoperative blood loss, postoperative bile leakage rate, and postoperative bowel obstruction rate. A Bayesian model was employed for the network meta-analysis, with heterogeneity and consistency checks as well as publication bias assessments. Furthermore, a retrospective cohort study was conducted on 72 CCC patients who underwent surgery between January 2010 and January 2025 at two medical centers [60 cases in the open surgery group [OSG] and 12 cases in the laparoscopic surgery group [LSG]]. These data were incorporated into the meta-analysis to evaluate consistency with prior findings.ResultsThe 28 studies (2007–2025) included two three-arm and 26 two-arm studies. Newcastle-Ottawa Scale assessment identified biases in selection and follow-up in some studies. Open surgery had the shortest operative time (MD = −1.101 vs. laparoscopic, 95% CI: −1.368 to −0.834; MD = −1.39 vs. robotic, 95% CI: −1.69 to −1.09), followed by robotic-assisted, then laparoscopic surgery. Robotic-assisted surgery had the shortest hospital stay (MD = −1.98 vs. open, 95% CI: −2.72 to −1.19), followed by laparoscopic. Laparoscopic surgery had the least blood loss (MD = 46.76 vs. open, 95% CI: 10.36–83.64), followed by robotic-assisted. Robotic-assisted surgery had the lowest bile leakage rate; laparoscopic had the lowest bowel obstruction rate (OR = 0.11 vs. open, 95% CI: 0.01–0.6). Retrospective data showed OSG had shorter operative time (3.52 ± 0.82 vs. 5.61 ± 1.24 h, P < 0.01), longer hospital stays (15.98 ± 4.99 vs. 12.92 ± 2.15 days, P < 0.05), and greater blood loss (90.45 ± 62.29 vs. 46.00 ± 26.52 ml, P < 0.05) than LSG, with no significant difference in complications. Updated meta-analysis confirmed consistent rankings.ConclusionsRobotic-assisted surgery excels in reducing hospital stay and bile leakage, laparoscopic surgery minimizes blood loss and bowel obstruction, while open surgery is fastest but inferior in other outcomes. These findings guide CCC surgical decisions, though randomized trials are needed.